Jakowa Galinkowskiego klucz do literatury europejskiej — pro et contra - Dąbrowska, Magdalena (Rusycystyczne Studia Literaturoznawcze, 2014)
Jakov Galinkovsky (Galenkovsky; 1777—1815) was a writer, poet, literary critic, translator, publisher of the periodical “Corypheus, or the key to the European literature” that contains a review of the history of the European literature from the ancient times to the 19th century. The article consists of three parts: 1. The presentation of works by Jakov Galinkovsky (novels, their links with sentimentalism and its criticism, the poem [Imitation of a Satire of V. Kapnist]), 2. The image of the West-European literature in the periodical “Corypheus, or the key to the European literature,” 3. The reviews of the periodical “Corypheus, or the key to the European literature” in the Russian periodicals in the early 19th century (“Moskovsky Mercury,” “Severny vestnik,” etc.).